The Influence of Teachers Competence and Organizational Climate on Teachers of English Performance - Astri Riance (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The objective of this study was to determine the effect of teachers competence and organizational climate on teacher of English performance at Senior High School in Lubuklinggau. This research used quantitative research method. Based on the result of data analysis and discussion, it can be concluded that 1) There was an influence of teachers’ competence on teachers of English performance at Senior High School in Lubuklinggau it can be seen from the value of t= 6.608 greater than the value of t table (1.991) with a significant level of sig = 0.05, 2)There was an influence of the organizational climate on teacher of English performance at Senior High School in Lubuklinggau it can be seen from the value of t = 4.197 is greater than the value of t table (1.991) with a significant level sig = 0.005, 3) There was an influence of teacher competence and organizational climate on Teacher of English performance at Senior High School in Lubuklinggau. It can be seen from the value of F count obtained 11.901 > F table = 2.33 and significant level simultaneously sig F was 0.000. From this result it can be concluded that there was significant influence of teachers competence and organizational climate on teachers of English performance at Senior High School in Lubuklinggau. Keywords: teacher competence, organizational climate, teacher performance